Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1139/cjes-2018-0170
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Anatolian Orogenic Belt revisited (geology and evolution)

Yücel Yılmaz

Abstract: The Southeast Anatolian Orogenic Belt consists of the Arabian Platform, a zone of imbrication, and a nappe zone. The Arabian Platform is represented by a thick marine succession. The zone of imbrication is a narrow belt sandwiched between the Arabian Platform and the nappes. The nappes are the highest tectonic unit. They consist of two continental slivers separated by ophiolitic associations representing oceanic environments. They were involved in the orogenic development and formed two metamorphic belts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 59 publications
0
35
0
1
Order By: Relevance
“…Data discussed in the preceding paragraphs lead to infer that the development of the Adana plain, the AİBC, and the surrounding mountains are genetically associated with the two groups of tectonic events; (1) the evolution of the SAOB (Yılmaz 1993(Yılmaz , 2019McKay and Robertson 2013) and 2the tectonic activities in the Eastern Mediterranean (Le Pichon and Kramer 2010; Özeren and Holt 2010;Robertson et al 2012;Harrison et al 2012;Schildgen et al 2012a, b;Kinnaird and Robertson 2013;Yılmaz 2019).…”
Section: Discussion On the Tectonic Development Of The Adana Plain Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Data discussed in the preceding paragraphs lead to infer that the development of the Adana plain, the AİBC, and the surrounding mountains are genetically associated with the two groups of tectonic events; (1) the evolution of the SAOB (Yılmaz 1993(Yılmaz , 2019McKay and Robertson 2013) and 2the tectonic activities in the Eastern Mediterranean (Le Pichon and Kramer 2010; Özeren and Holt 2010;Robertson et al 2012;Harrison et al 2012;Schildgen et al 2012a, b;Kinnaird and Robertson 2013;Yılmaz 2019).…”
Section: Discussion On the Tectonic Development Of The Adana Plain Tmentioning
confidence: 99%
“…The northward advance of the Arabian Plate continued after the collision. The remnant seas that followed the ocean's demise survived until the late Miocene (Yılmaz 1993(Yılmaz , 2019. The evidence for this is the development of the E-W trending flysch belts accumulated in front of the nappes during the Miocene (Yilmaz 1993(Yilmaz ,2019Siyako et al 2013).…”
Section: Discussion On the Tectonic Development Of The Adana Plain Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Polat, Longstaffe, et al (2018) highlighted the similarity between Phanerozoic anorthosite‐bearing ophiolites and Archean anorthosite‐bearing layered intrusions and concluded that the latter formed in arc‐rift or back‐arc geodynamic settings. Some of the Phanerozoic ophiolites that formed during the opening and closure of the Tethys oceans (Paleo‐ and Neo‐Tethys), and therefore, the creation of the Alpine, Dinaride, Balkan, Taurus, Pontide, Caucasus, Zagros, and Himalayan mountain ranges (Dilek & Furnes, 2009; Şengör, 1979, 1990; Şengör et al, 2019; Yılmaz, 2019) contain anorthosites and share petrological and geochemical similarities with Archean anorthosite‐bearing layered intrusions (see Polat, Longstaffe, et al, 2018). The petrological and geochemical similarities between these Tethyan ophiolites and Archean anorthosite‐bearing layered intrusions include the fact that they both contain anorthosite‐bearing mafic to ultramafic cumulate sequences that are spatially associated with pillow basalts, and both have depleted, subduction‐derived N‐MORB‐normalized trace element patterns exhibiting variably negative Nb‐Ta‐Ti anomalies and high large‐ion‐lithophile abundances (Ashwal & Bybee, 2017; Dilek & Thy, 2009; Dilek & Furnes, 2009, 2011, 2014; Pearce, 2014; Polat, Longstaffe, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%